1997
DOI: 10.3109/02770909709067222
|View full text |Cite
|
Sign up to set email alerts
|

Results of the First U.S. Double-Blind, Placebo-Controlled, Multicenter Clinical Study in Asthma with Pranlukast, a Novel Leukotriene Receptor Antagonist

Abstract: Pranlukast (SB 205312; ONO-1078), a potent, orally active selective cysteinyl-leukotriene receptor antagonist (LTRA), was developed in Japan for the treatment of asthma. This article reports results of the initial U.S. clinical evaluation of pranlukast. The primary objective of this multicenter study was to evaluate the safety and tolerability of pranlukast administered at doses of 337.5 mg b.i.d. and 450 mg b.i.d. in 65 patients with mild to moderate asthma. Pranlukast, a novel LTRA, is safe and well tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…[109][110][111] Use of these agents improves baseline lung function, reduces symptoms, and lessens the requirement for rescue medications. High-dose zafirlukast therapy for 6 weeks significantly improved asthma control over placebo in patients who were refractory to high-dose inhaled corticosteroid therapy.…”
Section: Cysteinyl Lt Receptor Antagonists In Clinical Asthmamentioning
confidence: 99%
“…[109][110][111] Use of these agents improves baseline lung function, reduces symptoms, and lessens the requirement for rescue medications. High-dose zafirlukast therapy for 6 weeks significantly improved asthma control over placebo in patients who were refractory to high-dose inhaled corticosteroid therapy.…”
Section: Cysteinyl Lt Receptor Antagonists In Clinical Asthmamentioning
confidence: 99%
“…Pranlukast (8-[p-(4-phenylbutyloxy)benzol] amino-2-[tetrazol-5-yl]-4-oxo-4H-1-benzopyran hemihydrate) is a selective cysLT 1 receptor antagonist [7]. It is effective in reducing bronchial hyperresponsiveness and allergen-induced bronchoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LTRA decreases airway inflammation by suppression of LT action [7, 8]. Different reports have shown that treatment of persistent asthmatics with LTRA resulted in 6–14% (in the range) improvement of forced expiratory volume in 1 s (FEV 1 ) and/or peak expiratory flow rate (PEFR), and decreases of 19–46% in nocturnal symptoms, 13–27% in daytime symptom score and 10–31% in the use of rescue β 2 -agonists [9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20]. Based on these studies, the revised versions of the Global Initiative for Asthma published in 1998 and 2002, respectively, both recognize LTRA in combination with corticosteroids as a maintenance therapy in the treatment of asthma [2].…”
Section: Introductionmentioning
confidence: 99%